Pressure Transient Analysis of Dual Fractal Reservoir. (17th September 2013) - Tan, Xiao-Hua; Li, Xiao-Ping; Liu, Jian-Yi; Tang, Chuan; Li, Jin-man
Abstract : A dual fractal reservoir transient flow model was created by embedding a fracture system simulated by a tree-shaped fractal network into a matrix system simulated by fractal porous media. The dimensionless bottom hole pressure model was created using the Laplace transform and Stehfest numerical inversion methods. According to the model's solution, the bilogarithmic type curves of the dual fractal reservoirs are illustrated, and the influence of different fractal factors on pressure transient responses is discussed. This semianalytical model provides a practical and reliable method for empirical applications.